The Effect of High-Intensity Interval Training (HIIT) on Brain-Derived Neurotrophic Factor Levels (BNDF): A Systematic Review - Milosz Mielniczek; Tore Kristian Aune (Brain Sciences)
Background/Objectives: High-intensity interval training (HIIT) alternates short periods of intense exercise with recovery, effectively enhancing cardiorespiratory fitness, endurance, and strength in various populations. Concurrently, brain-derived neurotrophic factor (BDNF) supports neuronal resilience and activity-dependent plasticity, which are vital for learning and memory. This study aims to systematically review changes in BDNF levels in response to HIIT, with three primary objectives: evaluating the benefits of HIIT for BDNF modulation, assessing methodological quality and the risk of bias in reviewed studies, and identifying patterns in BDNF response based on HIIT protocols and population characteristics. Methods: Comprehensive database searches were conducted in PubMed and SPORTDiscus to identify relevant studies published up to April 2024. Given the diversity in study designs and outcomes, a narrative synthesis was performed rather than a meta-analysis. Bias was evaluated using visualization tools such as RobVis, and the review was conducted by a single researcher, which may limit its comprehensiveness. Results: Twelve studies met the inclusion criteria, with most indicating significant increases in BDNF levels post-HIIT, suggesting HIIT’s potential to enhance neuroplasticity and cognitive functions. However, variations in BDNF responses were observed across different HIIT protocols and study populations. Some studies reported decreases or no change in BDNF levels, reflecting the complex regulation of BDNF influenced by factors such as exercise intensity, duration, and individual variability. Conclusions: HIIT shows promise as an intervention for increasing BDNF levels, with potential benefits for brain health and cognitive function. These findings underscore the need for further research to confirm the optimal conditions under which HIIT can effectively enhance neurological outcomes. Future studies should explore standardized HIIT protocols and the long-term impact of HIIT on BDNF and neuroplasticity.